Penerapan Strategi Peta Konsep Dan Peta Pikiran Ditinjau Dari Minat Belajar Terhadap Prestasi Belajar Fisika - Wajdi, Badrul; Hizbi, Tsamarul (Kappa Journal, 2017)
The objectives of this research were know: 1) the effect of concept and idea map strategy reffering to learning intreset on the physics learning achivement at VIII grade of SMP Laboratorium Hamzanwadi Pancor in the school year 2105-2016; 2) the effect of student high and low learning intreset on physics learning achievement about sense of sight and optic equipment material at VIII grade of SMP Laboratorium Hamzanwadi Pancor in the school year 2105- 2016; 3) the effect of intraction between concept and idea map strategy with students’ intrest on physics learning achievement about sense of sight and optic equipment material at VIII grade of SMP Laboratorium Hamzanwadi Pancor in the school year 2105-2016. This research was experiment utilizing 2x2 factorial design. The population of research was whole student at VIII class utilizing VIII A class as the experiment and VIII B class as the control class. The data collections technique applied were test and questionnaire. The result hypothesis testing showed that: 1). There was effect of concept map and idea map strategy on the students’ learning achievement; 2). There was effect of students’ high and low basic ability on the students’ learing achievement; 3). There was no intraction concept and idea map strategy with students’ interest on the studens’ learning achievement. The result of advance testing utilizing scheff tsting showed; 1). The students’ learning achievement who thought using concept map strategy was not given better effect than idea map strategy; 2). The students’ learning acheivement that has high learning interest was given better effect than low learning interest.